An experimental study on the heat transfer performance of a prototype molten-salt rod baffle heat exchanger for concentrated solar power. (1st August 2018) - Qiu, Yu; Li, Ming-Jia; Wang, Wen-Qi; Du, Bao-Cun; Wang, Kun
Abstract: A prototype rod baffle shell-and-tube heat exchanger (RB-STHX) was proposed for concentrating solar power (CSP). For investigating the heat transfer of molten salt in the shell side, the RB-STHX was experimentally studied. A ternary salt Hitec and an oil were adopted as the heat transfer fluids in the shell and tube sides, respectively. Experimental data was firstly obtained when the salt temperature is 212.7–279.6 °C with the Prandtl number of 14.2–23.3. The flow of the salt is turbulent with the Reynolds number ( Re ) of 2697–12, 517. The average heat transfer rate ranges from 117 kW to 364 kW. Then, the experimental data was compared with two exiting correlations. The results indicate that an average error of −9.1∼-12.3% between the Nusselt numbers predicted by the two correlations and the experiment data was found. Finally, for predicting the heat transfer of the molten salt in the shell side more accurately, two modified heat transfer correlations which show satisfactory agreements with the experimental data were developed. The average deviations under different Re between the experiment data and the modified correlations are around ±4.4∼±4.6%. Results from current study offer reliable experimental data, useful correlations and helpful guidance for the design of realistic molten-salt RB-STHXs in the CSP systems. Highlights: A prototype rod baffle heat exchanger is designed and fabricated for the CSP. Heat transfer of molten salt in the shell side is experimentally investigated. Relatively large errors between exiting correlations and experiment data are found. Modified correlations are fitted, and the average deviations are within ±4.6%.